Karnataka land reforms act, 1961: Karnataka act no.10 of 1962 - Puliani, Yashpal (Bangalore Karnataka law journal publications, 2023)
Karnataka land reforms rules, 1974: as amended by RD 07 CCRV 2022, dated 18-11-2022
Keywords: Karnataka law journal